2014
DOI: 10.1021/jp503037q
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Preferential Pu(IV) Extraction over U(VI) by N,N-Dihexyloctanamide versus Tri-n-butyl Phosphate: Evidence through Small Angle Neutron Scattering and DFT Studies

Abstract: Straight chain amide N,N-dihexyloctanamide (DHOA) has been found to be a promising alternative extractant to tri-n-butyl phosphate (TBP) for the reprocessing of irradiated uranium- and thorium-based fuels. Unlike TBP, DHOA displays preferential extraction of Pu(IV) over U(VI) at higher acidities (≥3 M HNO3) and poor extraction at lower acidities. Density functional theory (DFT) based calculations have been carried out on the structures and relative binding energies of U(VI) and Pu(IV) with the extractant molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…The most predominant species were 1 : 1 and 1 : 2. The structure of UO 2 (NO 3 ) 2 -$2TBP was similar to that reported in the literature, 35 in which two TBP molecules coordinated with uranyl moiety O]U]O at the equatorial plane. For the 1 : 1 species, TBP also coordinated to the uranium from the equatorial plane of the uranyl moiety, and the angle of N/U/N was approximately 153 , bending towards the side without TBP.…”
Section: Simulation Without H 2 Osupporting
confidence: 83%
“…The most predominant species were 1 : 1 and 1 : 2. The structure of UO 2 (NO 3 ) 2 -$2TBP was similar to that reported in the literature, 35 in which two TBP molecules coordinated with uranyl moiety O]U]O at the equatorial plane. For the 1 : 1 species, TBP also coordinated to the uranium from the equatorial plane of the uranyl moiety, and the angle of N/U/N was approximately 153 , bending towards the side without TBP.…”
Section: Simulation Without H 2 Osupporting
confidence: 83%
“…[30,31] A similar combination of functional and basis sets was previously used to predict accurate geometries and energetics for several uranyl complexes. [24,[32][33][34][35][36][37][38][39] To verify whether the obtained structures correspond to the potential energy minima, analytical frequency calculations were carried out using the AOFORCE module as implemented in TURBOMOLE version 6.3.1 (Karlsruhe, Germany). [40] Finally, binding free energies were calculated at 298.15 K after incorporating thermal and non-thermal corrections into the electronic energies.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Correspondingly, through DFT calculations, Chandrasekar et al found that the selectivity of tri- sec -butyl phosphate (TsBP) for U­(VI) is much higher than that for Th­(IV), which is related to the combination of structural and electronic effects near the binding site. Likewise, Kong, Verma, and Wang et al , examined the interactions between various extractants and elements in spent nuclear fuel by DFT. Mechanisms of extractants to selectively separate plutonium, uranium, actinides, and lanthanides are explained from the microscopic level by analyzing the electronic structure and bonding nature of complexes.…”
Section: Introductionmentioning
confidence: 99%